Effectiveness of Javanese Turmeric (Curcuma Xanthorrhiza Roxb) to Improve Eating Behavior Among Anorexia Children in Bogor - Rukmaini, Rukmaini; Siauta, Jenny Anna; Adegi, Luthfiyah (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Anorexia or lack of desire to eat and loss of appetite is a common issue among children. Some herbs were successfully tested to increase eating behavior, including Javanese turmeric or temulawak. This study aimed to examine the effectiveness of Javanese turmeric on eating behavior scores among children with anorexia. The study was done in Bogor Regency in January 2024. There were 30 children aged 4 to 6 years included in this study who were selected by the non-probability sampling method. Among them, 15 children were categorized into intervention or case group, and the rest as control group. The intervention is giving Javanese turmeric pudding. Before and after giving the intervention, the parents were asked to answer the children's eating behavior questionnaire (CEBQ). The finding by using paired and independent t-tests in this study revealed that Javanese turmeric is significantly effective in improving eating behavior (p-value <0.05) comparing pre and post-tests. This study can encourage the policymakers to do more education and promote of effectiveness of Javanese turmeric for health at the village and school levels. Future studies can improve the food variety made from Javanese turmeric to be more interesting for children.